PENINGKATAN KUALITAS DAN KAPASITAS USAHA DENDENG BABI DI SIKUMANA, KOTA KUPANG - Meity Marviana Laut; Larry R. W. Toha; Julianty Almet; Dewi Djungu; Yohanes Simarmata (Jurnal Media Tropika, 2021)
The small food processing industry in Kupang City has increased in recent years. One of the evolving food processing industries is pork processing. Pork jerky is one of the processed pork products and is classified as a new product for the community in Kupang City. When compared to se'i, pork jerky is not very popular among people in NTT. This can be because there are still very few UMKMs (Micro Small and Medium-sized enterprises/MSMEs) that produce pork jerky.UMKMs pork jerky Debali is one of the small business units in Kupang City that produce pork jerky. In addition to being marketed in Kupang City, Debali pork jerky products have also been marketed out of Kupang City. But like other UMKMs, Debali experiences production process problems such as a simple production process that takes a relatively long production time, the number of products is still insignificant, simple product packaging and vacuum packaging products are not available which have a longer shelf life. Community service activities to transfer science and technology (Ipteks) are carried out to improve the quality and capacity of Debali pork jerky business through counseling, gas ovens operation training as an alternative to drying jerky, packaging jerky with modern packaging and vacuum packaging, as well as assistance in marketing and business analysis.